PERBANDINGAN HASIL RIAS KARAKTER LUKA TIGA DIMENSI PADA TANGAN MENGGUNAKAN LATEKS DAN KAPAS - Hendri, Jeki - (journal of residu, 2019)
Research aims for 1) knowing the results of the use of latex on the character dressing three-dimensional torn wound on hand, 2) the use of cotton on the form of three-dimensional torn wounds on the hands, 3) The difference of makeup of the character torn wound three dimensional Use of latex with the use of cotton. This research is a pseudo experimental research (quasi experiment). The variables in this study consist of two variables i.e. a free variable (X) and a bound variable (Y). The research procedure consists of three phases namely the research preparation phase, the treatment phase and the after treatment stage. Data types use primary data whereas for data sources using 10 samples. Data collection techniques are done by observation and documentation. The data analysis technique in this study is to use a descriptive statistical technique with percentages. The results showed that the use of Latex in accordance with the indicator is from the endurance aspect shows an average of 9.43 categories of resistance, the ease of average application 10.57 category is very easy, and from the aspect of similarity of color shows An average of 9.29 similar categories. Using cotton in accordance with the indicator is from the endurance aspect shows an average of 7.29 categories quite resilient, the ease of application showed an average of 6.57 quite easily and from the aspect of similarity color shows the average of 6.86 categories quite similar. There is a comparison of durability, ease of application and the color resemblance to applying latex and cotton to the three-dimensional torn wound of character dressing in the makeup and beauty students at the Padang State University.